Hop a little, jump a little! - Kubler, Annie, 1960- (Swindon, U.K. ; Auburn, Me. Child's Play, 2010)
Simple rhymes describe the different ways babies and toddlers can move around.
Title from cover.
On board pages.
Music printed on back cover.
Keywords: Infants -- Juvenile fiction; Exercise -- Juvenile fiction